Early Children’s Healthy Behavior - Astuti, Apriliana Kuntoro (Indonesian Journal of Early Childhood Education Studies, 2017)
Early childhood is the investment of the nation, because they are the future generation. The quality of the nation in the future is determined quality early age children today. Efforts to improve the quality of human resources to do since the early systematic and continuous. Growing development of optimal early childhood depends on healthy behaviors that do. Healthy behaviors observed are nutrients as needed, regular exercise, rest and enough sleep, perform dental and oral care, personal hygiene and the environment, as well as to prevent accidents. The purpose of this study is to describe the healthy behaviors early childhood in the village of Batur sub district Getasan as a recommendation for early childhood institutions to be followed up nearby. Early childhood institution as a partner for parents should educate about healthy behaviors early childhood and into second place for the conduct of habituation healthy behaviors. Because research shows that healthy behavior is not implemented perfectly by the parents to be in a range adequate criteria.